Extraction of Jatropha curcas fruits for antifungal activity against anthracnose (Colletotrichum gloeosporioides) of papaya - Rahman, Md. Mukhlesur; Ahmad, Siti Hajar; Tengku Muda Mohamed, Mahmud; Ab. Rahman, Mohamad Zaki (Academic Journals, 2011)
Extracts from seeds and leaves of Jatropha curcas have shown molluscidal, insecticidal and fungicidal properties. J. curcas extracts were found to inhibit the mycelium growth of Colletotrichum musae that causes anthracnose disease in bananas. The antimicrobial activity of crude methanol extracts of J. curcas fruits, pulp and seeds were investigated. J. curcas fruits, pulp and seeds were collected from the farm of Universiti Putra Malaysia. The samples were air dried at ambient temperature, then oven-dried to remove the residual moisture. Equivalent amounts of each ground sample of the J. curcas fruits, pulp and seeds were soaked in methanol solvent and left to stand for 7 days before being filtered and evaporated. The extract was spread over potato dextrose agar (PDA) medium under an aseptic condition and incubated. The zone of inhibition of mycelial growth (mm) around the disc was measured. Both J. curcas seed and pulp extracts had higher antifungal activity than whole fruit extract. J. curcas seed extract showed significant antifungal activities with growth inhibition zone of 5.6 mm or equivalent to 78.87% inhibition followed by pulp with zone of 7.4 mm or equivalent to 72.07%, and whole fruits with zone of 14.2 mm or equivalent to 46.42% as compared to the control with zone of 26.5 mm or equivalent to 100%. Active microbial components in J. curcas have the potential of an antifungal compound to control Colletotrichum gloeosporioides which causes anthracnose disease in papaya in vitro.